Penerapan Kegiatan Market Day untuk Menumbuhkan Jiwa Kewirausahaan Pada Anak Usia Dini - Utia Virli Susanti; Khoirul Amri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to describe the implementation of market day activities as a form of contextual learning and real experience in early childhood education institutions. In this study, participants in the Market Day activities that foster the entrepreneurial spirit of early childhood include teachers of Harapan Bangsa Early Childhood Education School, parents, children of Harapan Bangsa Early Childhood Education School and village officials and the community who participated in enlivening the event. This activity was carried out in Muara Bahan Village, RK 5 Rt 002 RW 004 Kuantan Singingi Regency, Riau. This school was chosen as the research location because they implement this activity every year as a mandatory program and teach children to be directly involved in contextual learning. The approach in this study used a qualitative approach used to find out and describe the facts of the events studied so as to facilitate the acquisition of objective data. The technique for selecting research subjects used a purposive sampling technique that was selected with consideration and purpose. The research subjects for researchers based on the criteria obtained during field visits include the fact that Harapan Bangsa PAUD is a school that implements Market Day activities with thorough implementation and preparation, and the principal and teachers allow interviews to be conducted after carrying out Market Day activities. The data collection techniques used in this study were interviews and observation. Observational research begins with recording, analyzing, and then drawing conclusions about the implementation and results of the program, as seen from the development of the businesses owned by the students. The next data collection technique used by the author was documentation. This documentation was used by the author to collect data on past events. Market day activities can provide a different learning experience from the usual method, but are still fun and involve children directly. Through these market day activities, children learn how to promote their products to buyers, they will experience being both buyers and sellers. The results of interviews conducted by researchers when visiting the school teacher explained that the Market Day activities had great enthusiasm and were warmly welcomed by parents, village mothers, and the surrounding community. It can be seen when children carry out their tasks and work together as a team in carrying out activities as sellers, it is clear that children learn from patience when waiting for buyers to arrive, patience in facing their role as sellers, and waiting their turn for buyers to come to the children's stand. Market day activities can provide a different learning experience from the usual way, but still fun and directly involve children. Through this market day activity, children learn how to promote their products to buyers, they will experience being both buyers and sellers. This market day program is implemented by schools as a program to develop students' skills in entrepreneurship. Market day activities for early childhood are usually held on a certain day that has been scheduled in advance. In this activity, the school must involve the role of their parents who make the products and the children who bring them to school.